2018
DOI: 10.3390/polym10101096
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fault Diagnosis System on Polymer Insulation of Power Transformers Based on 3-stage GA–SA–SVM OFC Selection and ABC–SVM Classifier

Abstract: Dissolved gas analysis (DGA) has been widely used in various scenarios of power transformers’ online monitoring and diagnoses. However, the diagnostic accuracy of traditional DGA methods still leaves much room for improvement. In this context, numerous new DGA diagnostic models that combine artificial intelligence with traditional methods have emerged. In this paper, a new DGA artificial intelligent diagnostic system is proposed. There are two modules that make up the diagnosis system. The two modules are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The optimal hybrid DGA feature subset (OHFS) was selected from three feature sets by using genetic algorithm-support vector machine-feature screen (GA-SVM-FS) model and used as input of the improved social group optimization (ISGO) optimized multi-SVM classifier to develop a transformer fault diagnosis model which achieved the highest fault diagnosis accuracy (92.86%) compared with other diagnostic models [24]. In addition, other scholars also used the SVM [49], relevance vector machine (RVM) [50] for transformer fault diagnosis and achieved good results.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal hybrid DGA feature subset (OHFS) was selected from three feature sets by using genetic algorithm-support vector machine-feature screen (GA-SVM-FS) model and used as input of the improved social group optimization (ISGO) optimized multi-SVM classifier to develop a transformer fault diagnosis model which achieved the highest fault diagnosis accuracy (92.86%) compared with other diagnostic models [24]. In addition, other scholars also used the SVM [49], relevance vector machine (RVM) [50] for transformer fault diagnosis and achieved good results.…”
Section: Introductionmentioning
confidence: 99%
“…A support vector machine (SVM), a form of supervised machine learning, has been widely applied for predicting creep behavior [28], moisture [29], etc. For instance, a 3-stage GA-SA-SVM has been used in dissolved gas analysis, with 90.36% accuracy [30]. Despite SVM involvement in numerous applications, the use of SVMs on a self-powered IPMC sensor is yet to be explored for healthcare applications.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with GA and PSO algorithms, the ABC algorithm was fit to optimize SVM (ABC-SVM) to improve the classification accuracy and complexity simultaneously. Huang et al [ 45 ] optimized the SVM parameters through ABC and realized the analysis of dissolved gases. Li et al [ 46 ] compared the four algorithms of ABC, GA, PSO, and ACO and found that the ABC algorithm has a simpler operation, fewer parameters, and stronger search capability than other algorithms.…”
Section: Introductionmentioning
confidence: 99%